2019
DOI: 10.1177/1367006919826865
|View full text |Cite
|
Sign up to set email alerts
|

Genericity in third language English: Acquisition pattern and transfer in ultimate attainment

Abstract: This study investigates the acquisition of genericity in advanced third language (L3) English. The learners are first language (L1) Moroccan Arabic–second language (L2) French adults. They completed an acceptability judgment task testing the interpretation of five count nominal types in noun phrase (NP)-level and sentence-level genericity: definite, indefinite and bare singulars, definite and bare plurals. The study defines the generic or non-generic status of every NP form in the learners’ L3 interlanguage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…The results showed that the L1 Moroccan Arabic learners of L3 English showed high accuracy with the definite singular with the NP generic and the bare plural with the NP generic and sentence generic, but low accuracy with indefinite articles, tending to use the definite plural despite the fact that this is not allowed in English. The results indicated that the Moroccan Arabic learners faced difficulties distinguishing between the NP generic and sentence generic as they did not demonstrate target-like performance (Hermas, 2020a). The results with L1 Moroccan Arabic learners of L2…”
Section: Previous Studies On the Acquisition Of Genericity In Englishmentioning
confidence: 83%
See 4 more Smart Citations
“…The results showed that the L1 Moroccan Arabic learners of L3 English showed high accuracy with the definite singular with the NP generic and the bare plural with the NP generic and sentence generic, but low accuracy with indefinite articles, tending to use the definite plural despite the fact that this is not allowed in English. The results indicated that the Moroccan Arabic learners faced difficulties distinguishing between the NP generic and sentence generic as they did not demonstrate target-like performance (Hermas, 2020a). The results with L1 Moroccan Arabic learners of L2…”
Section: Previous Studies On the Acquisition Of Genericity In Englishmentioning
confidence: 83%
“…Neither language group showed any L1 effect as both performed similarly with indefinite specific and generic references. The results of Alzamil's (2015) study can be contrasted with those of Hermas (2020aHermas ( , 2020b, who found that L1 Moroccan Arabic learners struggled with generic references with L2 French and L3 English due to L1 transfer. Crompton (2011) explored the types of errors made by Arabic learners of English in a corpus obtained from argumentative essays written by undergraduate students in their first and second years.…”
Section: Previous Studies On the Acquisition Of Genericity In Englishmentioning
confidence: 87%
See 3 more Smart Citations